O książce Henryka Kurczaba "Pogranicza sztuk i konteksty literatury pięknej" - Cyniak, Eugeniusz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2003)
Henryk Kurczab is a literature specialist, educator, lecturer and professor of Rzeszów Univertsity as well as Rzeszów College of Pedagogics. His book is a plenteous source of knowledge concerning dialogue, translatability and interaction of arts in the sense of semiotic ‘meaning’ and ‘sign’. The subject matter chosen by the author, i.e. arts correspondence, its own exemplification as well as interpretations, distinguish his work by individaulizing cognitive values.